Assessing efficiency of primary care services: methodological issues - Jaaman, Saifulsyahira; Rusli, Mohammad Farhan; Juni, Muhamad Hanafiah (Department of Community Health, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
The demand for high quality primary care services has been constantly increasing and it is likely to keep growing in the foreseeable future. Assessing efficiency of primary care services is crucial. The pursuit of efficiency in health systems should, therefore, be a central objective of decision makers and health managers. Measuring efficiency across institutions and across time is a critical element for improving the performance of health systems. The data for efficiency tool outlines key data categories and indicators necessary for assessing efficiency in the use of resource inputs, provides guidance on sources for these data and calculation of indicators. Applying this tool, managers will be better prepared to defend their budget requests providing evidence of internal efficiency while ensuring effective and efficient spending of monies that are allocated. There are a few methods that can be used for economic evaluation in assessing efficiency of primary care services. Economic efficiency of a service can be analyzed using non-parametric method (Data Envelopment Analysis) or parametric method - Stochastic Model (Frontier Approach).It can also analyzed based on production function – Cobb-Douglas Model or Trans Log Model. Using General Additive Model (GAM) where additive modelling techniques are the impact of the predictive variables. These methodologies come with several issues, whether the methods are suitable or not to be used in assessing efficiency of primary care services. This article will disclose the issues and the application of the economic efficiency methods used in primary care services.